On waves propagating over two submerged closely spaced poroelastic breakwaters. (August 2013) - Lan, Yuan-Jyh; Kuo, Yu-Shu; Hsu, Tai-Wen; Chen, Ching-Yu
In this paper, the problem of wave interactions created by two submerged closely spaced poroelastic breakwaters is investigated theoretically. An existing analytical solution is extended so as to be able to consider the problem subject to appropriate boundary conditions. The study domain is divided into seven sub-regions. Using general solutions for each region and matching kinematic and dynamic boundary conditions combined with an orthogonality condition, a set of simultaneous equations is developed; the individual equations being solved numerically. The analytical solutions are in agreement with the simplified cases of a submerged rigid breakwater, submerged permeable rigid breakwater and submerged poroelastic breakwater. Changes in the width of the two adjacent breakwaters, the effect of the permeability coefficient on wave profile, and the effect of materials and configurations of the breakwater on wave variation are the focus of the present paper. The presented results show that a large amount of energy is lost when the adjacent structures both have the same widths for a layer of a soft material with a high permeability. Different materials and shapes of structures can significantly influence the reflection coefficient.